Force production, balance controll, and muscle activation in different sitting positions - Pilot study for disabled sit sledge cross-country skiers - Rapp, W.; Lappi, T.; Lindinger, S.; Ohtonen, O.; Linnamo, V. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
Goal of the present study project is to get objective and valid information for the classification process in different sitting positions. In the first part methods such as EMG, video, and force recordings in combination with inertial sensor technologies will be utilized. In order to understand the neuromuscular patterns in specific situation of sitting Paralympic Nordic athletes, a first step was to evaluate this in healthy subjects. Based on this information the aim is to establish experimental setups for disabled. Furthermore differences between main sitting positions are to be analyzed.